Pengaruh Model Pembelajaran Mind Mapping Terhadap Minat Belajar IPS Kelas V - RiskhaYeni, Refi; Raharja, Hawwin Fitra; Salamah, Evi Rizqi (IJPSE Indonesian Journal of Primary Science Education, 2024)
Formal education at elementary school level appears several Problems related to social studies learning. The problems which often happened during social studies is about the standard of process. The goal of this research is to find out the interest of learning on social studies in type of economic action and in Indonesia on fifth grade students of Jombang before and after using mind mapping learning model. Also to understand any difference of mind mapping model. This research use quantitative approach by using pre-Experiental design method with one group pre-test and post-test design. Data collecting in this research in multiple choices question pre-test, post test and documentation.Based on t-test calculations which already decided based on pre-test and post-test result with t-test paired sample test then obtained t-calculate acquired value 3,341 and t-table is 2,093 and significant value (2 tailed) is 0,000 < 0,05 So result of t-calculate > t-table which means H accepted and H rejected. So, it can assumed that there is the effect of learning interest of social studies on fifth grade of Jatipelem state elementary school I diwelk, Jombang by using mind mapping learning model.